Case of Subcutaneous Leiomyosarcoma of the Scrotum Presenting as a Sebaceous Cyst in a 71-Year-old Man: A Case Report and Review of the Literature - Bankim Patel; Anup Vora; Nicolas Muruve (Urology Case Reports, 2014)
Leiomyosarcoma of the scrotum is a rare genital malignancy with approximately 35 reported cases in literature. We present a case of leiomyosarcoma of the scrotum in a 71-year-old man appearing as a sebaceous cyst that later developed ulcerations. However, because the irregular mass developed ulcerations, this should trigger one to consider that lesion is potentially malignant. The pathology report demonstrated malignant spindle cell neoplasm consistent with leiomyosarcoma, which tested positive for desmin and actin stains. On literature review, a study reported a 5-year survival rate of 50%-80%. The clinical features, diagnosis, histopathologic images, and treatment are reviewed.